Enhancing Accounting Systems: Unleashing User Potential through Perceived Utility and Security - Mudjiyanti, Rina; Kusbandiyah, Ani; Wardani, Susilo (Innovation Business Management and Accounting Journal, 2023)
The modernization of digital systems requires that every activity can be reached from various places, including financial activities. This study aims to prove whether there is an effect of perceived usefulness, perceived convenience of use, security, and system quality on the actual use of accounting information systems by mobile banking users. This study used a sample of students in Purwokerto, with the provision that a student uses more than one mobile banking, to assess the usefulness, convenience, security, and quality of the system, as well as satisfaction with using mobile banking. This activity increases when all the conveniences can be felt by mobile banking users in transactions. Respondents in this study are students who use more than one mobile banking. This is useful for assessing how satisfied students are with using mobile-banking applications. The results showed that perceived convenience and usefulness had no effect on the actual use of accounting information systems. While the variables of security and system quality have an influence on the actual use of accounting information systems.